A comparison of physiological intensity and psychological perceptions during three different group exercise formats - Gottschall, Jinger S.; Hastings, Bryce (Frontiers in Sports and Active Living, 2023)
Introduction Past research highlighted that group fitness is an ideal format to meet exercise prescription guidelines. To add, a group enhances exertion, enjoyment, and satisfaction. In the last five years, streaming (live classes on screen with other participants visible) and on demand (pre-recorded classes on screen without other participants visible) formats have grown in popularity. Our goal is to compare the physiological intensity and psychological perceptions of live group, live streaming, and non-live on demand classes. We hypothesize that live classes will have the greatest cardiovascular intensity, enjoyment, and satisfaction followed by streaming and finally on demand. Methods Fifty-four adults between 18–63 years, who regularly participate in group fitness classes, recorded their heart rate with a chest transmitter during a mixed-martial arts cardiovascular class on consecutive weeks in random order. We calculated the mean, identified the max, and extracted the top 300 values (5 min) for comparison between conditions. Results Following each class, the participants completed an online survey to evaluate their rate of perceived exertion, enjoyment, and satisfaction. Confirming our hypothesis, mean class heart rate and mean heart rate for the five minutes at the highest intensity were 9% greater during the live group format compared to both live streaming and non-live on demand (all values, p < 0.01). However, there was no difference in any heart rate variables between the streaming and on demand formats. Also, rate of perceived exertion, enjoyment, and satisfaction were all significantly greater during the live session compared to the home collections (all values, p < 0.05). Discussion Streaming and on demand group fitness formats are viable options for meeting exercise prescription guidelines. But physiological intensity and psychological perceptions were greater during the live class format.